2017
DOI: 10.1093/neuonc/nox160
|View full text |Cite
|
Sign up to set email alerts
|

Molecular differences in IDH wildtype glioblastoma according to MGMT promoter methylation

Abstract: MGMT promoter methylation status does not define a molecularly distinct glioblastoma subpopulation among untreated tumors. Progressive mMGMT glioblastomas and mMGMT tumors of patients with short survival tend to have more unfavorable molecular profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 35 publications
0
51
0
1
Order By: Relevance
“…The delineation of the right subgroups may also involve global methylation profiles and TERT status. 75 , 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The delineation of the right subgroups may also involve global methylation profiles and TERT status. 75 , 5 …”
Section: Discussionmentioning
confidence: 99%
“…TERT expression may be necessary to ensure the MGMT methylation related benefit to alkylating chemotherapy. 45 Overall, MGMT status testing without taking consequences is unsettling for patients, creates a lot of second consulting and finally undermines trust in our profession. On the other hand, testing offers the opportunity to safe patients a treatment with no or little chances for help plus offers options for alternatives, which should be based on further precision measures by looking for molecular lesions potentially relevant for targeted or immunotherapies (see Outlook).…”
Section: Adaptions/options To the Standard In Newly Diagnosed Patientmentioning
confidence: 99%
“…IDH wild-type glioblastoma can be subclassified into two robust prognostic and biological groups based on the status of MGMT promoter methylation (36,37). Among IDH wild-type glioblastomas in the discovery set, all 4 tumors with DLL3 expression in !50% of tumor cells were MGMT methylated.…”
Section: Dll3 Expression In Glioma Molecular Subtypesmentioning
confidence: 99%
“…Weller et al have also identified eight transcriptionally different groups (five IDH 1/2 mutant and three IDH 1/2 wild types) of glioma by analyzing transcriptome-wide data derived from primary tumor samples [13]. Recent studies have confirmed that IDH mutation can impair histone demethylation [14] and predict better survival for glioma patients [15, 16]. However, current molecular classification cannot ensure the precise diagnosis and personalized medicine for LGG patients.…”
Section: Introductionmentioning
confidence: 99%